Efficient encapsulation of toxic dyes from wastewater using several biodegradable natural polymers and their composites - Yeamin, M.B.; Islam, M.M.; Chowdhury, A.N.; Awual, Rabiul (ELSEVIER SCI LTD, 2021)
The removal of organic dyes from wastewater by innovative effluent treatment plant, which can truly clean the wastewater without leaving any fragments of dye species without generating secondary waste, is one of the prime challenges to the present world. The natural polymers were wheat flour, turmeric powder, pure starch, starch nanoparticles and some other forms of rice or wheat grains, while the synthetic polymeric adsorbents were polyaniline (PAni) and PAni/starch composites systematically studied for dyes adsorption. The cationic dye, methylene blue (MB), and an anionic dye, orange green (OG), from aqueous solutions through the adsorption using ten adsorbents of three categories; natural and synthetic polymers, and their composites, were widely investigated. The adsorbents either prepared or pre-treated were characterized using Fourier transform infra-red (FTIR) spectroscopy, scanning electron microscopy (SEM), X-ray diffraction spectroscopy (XRD) and differential thermal analyses techniques. The formation of PAni/starch composites was confirmed by the results of FTIR and thermal analyses. The SEM and XRD measurements were employed to determine the surface morphology and particle/crystallite size of the adsorbents. The degrees of adsorption of MB and OG on all adsorbents studied were evaluated by UV–visible spectroscopic technique. The cost effectiveness of the adsorbents studied was evaluated where the starch-based adsorbents are explored to be promising from economic and environmental viewpoints. The mechanism of adsorption of MB and OG dyes on starch-based adsorbents was also discussed.